Change management strategies for the success of lean adoption - Muhammad Shafee, Nur Ain Qistina (2022)
The failure in the lean adoption system is due to the disagreement of employees to follow the new ideas and misunderstanding of the employers towards the lean contributions. Therefore, there is a need to conduct a study on the introduction of appropriate strategies for the industries to follow to create a conducive environment for successful lean implementation. The objectives of this study are to investigate the barriers for the employees to accept the lean adoption in the company, establish the appropriate strategies for the employees to follow the lean implementations, and propose a conducive environment for successful lean implementations based on the change management concept. The scope of this study is to focus on the employees’ side of the company from various levels in the company organization. The questionnaires, with the Cronbach’s Alpha value of 0.84 which is more than 0.70 indicating the set of questions are reliable, are being used for the methodology and were distributed to 100 employees with 79% of response rate, which means the total respondents for this research is 79 respondents. For the data gathered, the frequency analysis and average index were being used. In consequence, the problems will be used in establishing the new strategies to increase the lean successful performance, creating a new medium that is more reliable. Finally, by using Jick’s change management method, as example promote the changes widely thus create a high awareness that the changes will be executed by circulate the advertisement months before the changes be executing and the change team as well should create a discipline set of rules to avoid any lousiness and provide a standard working or operations procedures in ensuring the changes will be done according to the actual working style in achieving a remarkable and victorious lean adaptation into the company.